The Priority Of Knowledgable People In Az-Zumar Verse 9 Perspectives Of Contemporary Interpretation - Ramadhani, Lintang; Zenrif, Fauzan; Hartanto, Rahmad Agus (DINAMIKA : Jurnal Kajian Pendidikan dan Keislaman, 2025)
This article discusses the virtues of knowledgeable people in Az-Zumar verse 9 which are discussed through the perspective of contemporary interpretation. This study aims to explore the meaning of ideal Islamic education, which not only increases the intellectual capacity of individuals but also forms good character and noble morals. Education in Islam is interpreted as a balanced process between the world and the hereafter, where knowledge becomes a light that illuminates the path to truth. This study uses a literature study approach by referring to primary sources from contemporary interpretation books, namely the interpretation of Al-Misbah, Al-Azhar, Asy-Syaamil fi Balaghatil Qur'an, and At-Tahrir wa At-Tanwir. The results of the study show that knowledgeable people have a higher degree in the sight of Allah. Education is able to form a young generation who are not only knowledgeable but also base their knowledge on their faith in Allah. The virtues of knowledgeable people include; being given guidance by Allah, given salvation from mistakes and humiliation, being able to distinguish between truth and falsehood, being independent in matters of religion and the world, and being obedient to science and Islamic law. This article also provides practical recommendations for parents and educators to instill the values ​​of knowledge and faith in their children's education so that they can grow into a pious generation, have noble character, and be ready to carry out their role as caliphs on earth. Thus, the primacy of knowledgeable people in the perspective of Az-Zumar verse 9 is an important basis for building a better civilization.